INVESTIGATION OF THE TOXICITY LEVEL OF HEAVY METALS RESULTED FROM THE MIGRATION OF LEACHATE POLLUTANTS ACROSS THE SOIL PROFILE OF A MUNICIPAL DUMPSITE (FUDMA JOURNAL OF SCIENCES, 2023)
In Nigeria and many developing countries, solid wastes are dumped in open landfills which are not provided with lining system to prevent leachate from infiltrating the soil into the groundwater. This study investigates the contents and concentration of heavy metal soil pollution in one of the dumpsite in the city of Kaduna, Nigeria. Six soil plumes were collected at different depth: 0, 25, 50, 100, 120 and 150 cm down the profiles and were analyzed for metallic elements. The instrumental neutron activation analysis (INAA) has been deployed to investigate the vertical distributions of heavy metals in soil profiles. The analysis revealed the presence of twenty-nine elements which shows a remarkable variation in concentration in all the soil samples. The mean concentrations of most of the detected elements were higher than their background values with the reference elements of Al, Fe, Ti showing the higher concentration in all samples. The mean concentration of Al, Fe, and Ti were 80868.3 ppm, 26260 ppm, and 3532.7 ppm respectively which are generally higher than their background values. Statistical analysis including the Pearson correlation of the elements and clustering analysis revealed a higher significant positive correlation among the samples. Repetitive order was noticed with some group of elements in all samples except A4. A significantly higher relationship displayed by all pair samples suggests a common anthropogenic source. There is a clear heavy polluted hotspot of Al, Fe, Ti, Potassium (K) and sodium (Na) as a result of anthropogenic activities that occurred in the study area.
Keywords: Dumpsite, instrumental neutron activation analysis, soil plume, and solid waste